Composite binder as well as preparation method and application thereof
By introducing MXene and sodium alginate into the binder, a three-dimensional network structure of composite binder is formed, which solves the problem of insufficient conductivity of traditional binders and significantly improves the electrochemical performance and energy density of the negative electrode of lithium-ion batteries.
Patent Information
- Application Number
- CN202411415437.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-07
AI Technical Summary
The existing binders are not conductive, resulting in insufficient electron ion transmission path of the negative electrode of lithium-ion batteries, affecting electrode performance.
Using a composite adhesive, the adhesive consists of a two-dimensional layered material MXene and sodium alginate, and forms a multi-layer porous aerogel structure through hydrogen bond cross-linking reaction to construct a three-dimensional network structure.
It improves the conductivity and electrochemical kinetic performance of the negative electrode of lithium-ion batteries, enhances the utilization rate of active substances, and improves the energy density and rate performance of the battery.
Smart Images

Figure CN119400866A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and more specifically to a composite adhesive and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) occupy an important position in the current market due to their high energy density and long life. They have the advantages of high operating voltage and environmental friendliness. As the negative electrode of lithium-ion batteries, compared with graphite (theoretical specific capacity: 372mAh g -1 ), silicon has 4200mAh·g -1 The high specific capacity of silicon is more than ten times that of graphite negative electrode materials. However, when silicon is used as the negative electrode of the battery, the electrons and ions in the electrode can only be slowly transferred in the system through the conductive additives, electrolyte and active material contact points. Due to the lack of efficient electron and ion transfer paths, the electrochemical kinetics of the electrode is reduced and the rate performance is poor. In addition, the lower electronic and ionic conductivity causes the utilization rate of active materials to decrease, resulting in a decrease in the specific capacity of the electrode.
[0003] The main function of the binder in the electrode is to bridge the active material, the conductive agent and the current collector to ensure the stability of the electrode structure. With the evolution of the active material, the function of the binder changes accordingly. Traditional binders such as polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), carboxymethyl cellulose (CMC) are not conductive and cannot improve the conductivity of the negative electrode. In order to improve the electrochemical performance of the electrode, it is urgent to build an electron ion transmission channel inside the electrode. Summary of the invention
[0004] The invention provides a composite binder and a preparation method and application thereof, which are used to solve the problem in the prior art that the binder has no conductivity and thus affects the performance of the electrode.
[0005] In a first aspect, the present invention provides a composite binder, which is a multi-layer porous aerogel structure, including a two-dimensional layered material MXene and sodium alginate inserted between the layers of the MXene material; and the surface of the composite binder is a three-dimensional network.
[0006] As a possible implementation manner, the mass ratio of the sodium alginate to the MXene material is 2 to 19:1.
[0007] As a possible implementation method, the MXene material is Ti3C2T x .
[0008] In a second aspect, the present invention provides a method for preparing the composite binder described in any possible implementation of the first aspect, comprising the following steps: mixing the colloidal solution of the MXene material and the sodium alginate solution under ice bath conditions, causing a hydrogen bond cross-linking reaction, and freeze-drying to obtain the composite binder.
[0009] As a possible implementation method, the preparation process of the colloidal solution of the MXene material includes the steps of: fixing the anode in an electrolytic cell, adding MXA phase powder, electrolyte filter membrane, and electrolyte in sequence; placing the cathode in the electrolytic cell to cause a selective etching reaction, and collecting the anode powder after the reaction is completed to obtain the colloidal solution of the MXene material.
[0010] As a possible implementation, the concentration of the colloidal solution of the MXene material is 2 to 5 mg / mL; the concentration of the sodium alginate solution is 3 to 4 mg / mL.
[0011] As a possible implementation, the conditions of the ice bath are: temperature 5-10°C, duration 7-10 h; the conditions of the freeze-drying are: temperature -10°C to -50°C, duration 48-60 h.
[0012] In a third aspect, the present invention provides an application of the composite binder described in any possible implementation of the first aspect or the composite binder prepared by the preparation method described in any possible implementation of the second aspect in a lithium ion battery.
[0013] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the active material of the negative electrode plate is obtained by mixing silicon in a mass ratio of 6:2:2, the composite binder described in any possible implementation of the first aspect or the composite binder prepared by the preparation method described in any possible implementation of the second aspect, and a conductive agent.
[0014] As a possible implementation method, the active material loading of the negative electrode sheet is 0.7-1.2 mg / cm 2 .
[0015] As a connection between active material, conductive agent and current collector, the binder has an intricate network. Therefore, the functionalized binder with a rapid electron ion transfer network can effectively improve the charge transfer capacity of the system, enhance the electrochemical power of the electrode, improve the utilization rate of the active material, and improve the energy density. The composite binder provided by the present invention can construct a composite binder 3D skeleton by introducing MXene into sodium alginate, promote the formation of LiF-rich SEI film, enhance the adhesion between the binder and silicon particles, and improve the stability of the pole piece during the charge and discharge process. Improve the stability and conductivity of the electrode, alleviate the volume expansion of the silicon negative electrode during the charge and discharge process, thereby improving the electrochemical performance of the electrode.
[0016] The preparation method of the composite binder provided by the present invention, the MXene material used is a two-dimensional layered carbide, the unique layered structure has a larger specific surface area, and the multilayer structure is more convenient for ion intercalation and transmission; the MXene material has good electrical conductivity, which is conducive to rapid electron transmission; the MXene material has excellent mechanical strength, which helps to maintain good electrochemical properties; the end groups such as -OH and -F on the surface are conducive to the formation of LiF-rich SEI film. Sodium alginate has good biocompatibility and degradability, and it contains rich oxygen functional groups (-OH, -COO- and =O), which can be easily cross-linked with MXene materials through hydrogen bonds; sodium alginate mainly plays a bonding role in the composite material, and at the same time plays a role in dispersing and intercalating the MXene material, forming a structure with a three-dimensional network surface and a multilayer and porous morphology. Too much addition of MXene material will reduce the material adhesion, and too little will lead to insufficient material conductivity, so the addition of sodium alginate and MXene material jointly affects the performance of the material.
[0017] The composite binder provided by the present invention is applied to the electrode, and the conductive agent is not required without sacrificing the energy density, thereby further improving the energy density of the entire device. When the composite binder provided by the present invention is applied to the silicon negative electrode of the lithium ion battery, it exhibits excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 This is a Fourier infrared spectrum of the composite adhesive A provided in an embodiment of the present invention.
[0020] Figure 2 This is a SEM image of the composite adhesive A provided in an embodiment of the present invention.
[0021] Figure 3 The conductivity diagram of the electrode piece prepared with composite adhesive A and adhesive D as the adhesive to be tested provided in the embodiment of the present invention.
[0022] Figure 4 The rate performance diagram of the electrode prepared using the composite binder A and the binder D as the tested binders provided in the embodiment of the present invention.
[0023] Figure 5 The cycle performance diagram of the electrode prepared with composite binder A and binder D as the tested binders at a current density of 0.5 A / g provided in the embodiment of the present invention.
[0024] Figure 6 The cycle performance diagram of the electrode prepared with composite binder A and binder D as the tested binders at a current density of 1 A / g provided in the embodiment of the present invention.
[0025] Figure 7 The electrochemical impedance diagram of the electrode prepared by using the composite binder A and the binder D as the tested binders provided in the embodiment of the present invention.
[0026] Figure 8 The constant current charge-discharge performance curve of the third cycle of the electrode piece prepared with the composite binder A and the binder D as the tested binders provided in the embodiment of the present invention.
[0027] Fig. 9 The cycle performance diagram of the electrode prepared with the composite binder B as the tested binder provided in the embodiment of the present invention at a current density of 0.5 A / g.
[0028] Fig.10 The cycle performance diagram of the electrode prepared with the composite binder B as the tested binder provided in the embodiment of the present invention at a current density of 1 A / g.
[0029] Fig.11 The cycle performance diagram of the electrode prepared with the composite binder B as the tested binder provided in the embodiment of the present invention at a current density of 2A / g.
[0030] Fig.12 The constant current charge-discharge performance curves of the first, second and third cycles of the pole piece prepared with the composite binder B as the tested binder provided in the embodiment of the present invention.
[0031] Fig.13 The cycle performance diagram of the electrode prepared with the composite binder C as the tested binder provided in the embodiment of the present invention at a current density of 0.5 A / g.
[0032] Fig.14 The cycle performance diagram of the electrode prepared with the composite binder C as the tested binder provided in the embodiment of the present invention at a current density of 1 A / g.
[0033] Fig.15 The cycle performance diagram of the electrode prepared with the composite binder C as the tested binder provided in the embodiment of the present invention at a current density of 2A / g.
[0034] Fig.16 The constant current charge-discharge performance curves of the first, second and third cycles of the electrode prepared with the composite binder C as the tested binder provided in the embodiment of the present invention.
[0035] Fig.17 This is a graph of the rate performance of an electrode prepared by using composite adhesive A as the adhesive to be tested without adding a conductive agent, according to an embodiment of the present invention.
[0036] Fig.18 The cycle performance diagram of the electrode sheet prepared by using the composite binder A as the tested binder without adding a conductive agent at a current density of 0.5 A / g provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In order to solve the problem that the binder in the prior art is not conductive and thus affects the electrode performance, the present invention provides a preparation experiment of a composite binder. Sodium alginate contains abundant oxygen functional groups (-OH, -COO- and =O), which can easily react with Ti3C2T x The end groups on the MXene surface form hydrogen bonds to interact with each other. Sodium alginate (SA) plays a major role in bonding in the composite material and also acts on the Ti3C2T x MXene plays the role of dispersion and intercalation, Ti3C2T x Too much MXene addition will reduce the material's adhesion, and too little will lead to insufficient conductivity of the material. Therefore, sodium alginate and Ti3C2T x The amount of MXene added jointly affects the performance of the material.
[0039] Furthermore, an embodiment of the present invention provides an application performance test experiment of a composite binder. It can be seen that the composite binder is applied to the silicon negative electrode of a lithium-ion battery, showing excellent rate performance and cycle stability.
[0040] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0041] Example 1
[0042] This embodiment provides a preparation experiment of a composite adhesive.
[0043] The anode is fixed in the electrolytic cell, and MXA phase powder, electrolyte filter membrane, and electrolyte are added in sequence; the cathode is placed in the electrolytic cell to cause a selective etching reaction. After the reaction is completed, the anode powder is collected to obtain a colloidal solution of MXene material. In the embodiment of the present invention, Ti3C2T x As MXene materials (Ti3C2T x MXene). It should be noted that due to the Ti3C2T x MXene needs to be stored at low temperatures, and direct drying may cause the material to pile up and aggregate, resulting in poor quality, including reduced pore structure and fewer active sites.
[0044] 680 g of sodium alginate was dissolved in 200 mL of deionized water to obtain sodium alginate solution A. 40 mL (concentration of 3 g / mL) of Ti3C2T x The MXene colloidal solution was stirred for 8 h and freeze-dried to obtain composite binder A.
[0045] 680 g of sodium alginate was dissolved in 200 mL of deionized water to obtain sodium alginate solution B. 98 mL (concentration of 3 g / mL) of Ti3C2T x The MXene colloidal solution was stirred for 8 h and freeze-dried to obtain composite binder B.
[0046] 680 g of sodium alginate was dissolved in 200 mL of deionized water to obtain sodium alginate solution C. 12 mL (concentration of 3 g / mL) of Ti3C2T x The MXene colloidal solution was stirred for 8 h and freeze-dried to obtain composite binder C.
[0047] Sodium alginate was used as the binder D.
[0048] Example 2
[0049] This embodiment provides an application performance test experiment of an adhesive.
[0050] Nano silicon powder (Si), the binder to be tested and the conductive carbon black (SuperP) were fully ground and mixed in a mass ratio of 6:2:2 to obtain a slurry, which was evenly coated on the current collector copper foil with a carbon layer. After drying, the slurry was cut into electrode sheets with a diameter of 10 mm as the negative electrode sheet. The lithium sheet was used as the comparison electrode. The active material loading was maintained at 0.7-1.2 mg / cm 2 . CR2032 button cells were assembled in a glove box using polypropylene (PP) film as the separator, 1 M lithium hexafluorophosphate (LiPF6) as the solute and a mixed solution of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 1:1 as the solvent as the electrolyte and left to stand for 8 h.
[0051] In this example, the composite binders A to D prepared in Example 1 were used as the binders to be tested, and batteries A to D were prepared. The electrochemical properties of the batteries were tested and the results were as follows: Figures 1 to 16 Results shown.
[0052] Depend on Figure 1 It can be seen that the composite binder A was successfully prepared, sodium alginate (SA), composite binder A (SA@Ti3C2T x )、Ti3C2T x MXene at 3230.6cm -1 、3411.3cm -1 、3431.1cm -1 Derived from -OH stretching vibration; at 2929.3cm -1 and 2934.1cm -1 Corresponding to -CH stretching vibration; at 1590.6, 1615.3 and 1620.5 cm -1 Shown is the asymmetric stretching of COO; at 1404.4 cm -1 and 1418.7cm -1 Derived from the symmetric stretching of COO; peak 1025.5cm -1 and 1028.6cm -1 Represents CO stretching vibration. Relative to Ti3C2T x MXene, SA@Ti3C2T x MXene at 3230.6cm -1 The peak shifts to a lower wave number and becomes weaker, which may be due to the intercalation of sodium alginate and Ti3C2T x The interaction between the functional groups of MXenes shows that sodium alginate and Ti3C2T x MXene was successfully compounded.
[0053] Depend on Figure 2It can be seen that the composite binder A has a three-dimensional network multilayer and porous morphology, which is composed of a large amount of sodium alginate inserted into Ti3C2T x MXene layers penetrate and support each other.
[0054] according to Figure 3 It can be seen that the composite adhesive A greatly improves the conductivity of the electrode on the basis of the adhesive D as the adhesive.
[0055] according to Figure 4 It can be seen that the specific capacities of composite binder A and binder D as binders at current densities of 0.2, 0.5, 1, 2.0, and 5.0 A / g are 3450.45, 2407.71, 1932.41, 1545.27, and 1020.26 mAh / g and 3214.26, 1739.49, 1235.46, 895.04, and 577.24 mAh / g, respectively, indicating that Ti3C2T x MXene has superior rate performance compared to binder D.
[0056] according to Figure 5 It can be seen that the specific capacities of composite binder A and binder D as binders after 400 cycles at a current density of 0.5 A / g still retain 808.1 and 406.6 mAh / g, respectively, indicating that Ti3C2T x MXene has excellent cycling performance compared to binder D.
[0057] according to Figure 6 It can be seen that the specific capacities of composite binder A and binder D as binders after 425 cycles at a current density of 1 A / g are retained at 1247.01 and 878.54 mAh / g respectively.
[0058] according to Figure 7 It can be seen that the composite binder A and binder D are used as binders, Ti3C2T x MXene has a smaller electrochemical impedance than binder D.
[0059] according to Figure 8 It can be seen that the discharge specific capacities of the electrodes prepared with composite binder A and binder D in the third cycle at a current density of 0.2 A / g are 2681.18 and 2402.18 mAh / g respectively.
[0060] according to Figures 9 to 16 It can be seen that after adding Ti3C2T x When the mass proportion of MXene is 30% and 5%, the battery still has excellent electrochemical performance.
[0061] Example 3
[0062] This embodiment provides an application performance test experiment of an adhesive.
[0063] Nano silicon powder (Si) and the binder to be tested were fully ground and mixed at a mass ratio of 9:1 to obtain a slurry, which was evenly coated on the current collector copper foil with a carbon layer. After drying, it was cut into electrode sheets with a diameter of 10 mm as the negative electrode sheet. The lithium sheet was used as the comparison electrode. The active material loading was maintained at 0.7-1.2 mg / cm 2 . CR2032 button cells were assembled in a glove box using polypropylene (PP) film as the separator, 1 M lithium hexafluorophosphate (LiPF6) as the solute and a mixed solution of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 1:1 as the solvent as the electrolyte and left to stand for 8 h.
[0064] In this example, the composite binder A prepared in Example 1 was used as the binder to be tested, and a battery was prepared and its electrochemical performance was tested. Figure 17-18 Results shown.
[0065] Depend on Fig.17 and Fig.18 It can be seen that without adding a conductive agent, the initial charge and discharge efficiency of the battery can reach 84.93%, and after 250 cycles, it still retains a specific capacity of 257 mAh / g. That is, without adding a conductive agent, the battery prepared with the binder provided by the present invention still has better performance.
[0066] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0067] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A composite adhesive, characterized in that: A multi-layer porous aerogel structure, comprising a two-dimensional layered material MXene and sodium alginate inserted between the layers of the MXene material; Furthermore, the surface of the composite adhesive is in a three-dimensional network shape.
2. The composite adhesive according to claim 1, characterized in that: The mass ratio of the sodium alginate to the MXene material is 2 to 19:
1.
3. The composite adhesive according to claim 1, characterized in that: The MXene material is Ti3C2T x .
4. The method for preparing the composite adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: The colloidal solution of the MXene material and the sodium alginate solution are mixed under ice bath conditions to undergo hydrogen bond cross-linking reaction, and freeze-dried to obtain the composite binder.
5. The preparation method according to claim 4, characterized in that: The preparation process of the colloidal solution of the MXene material comprises the following steps: The anode is fixed in the electrolytic cell, and MXA phase powder, electrolyte filter membrane, and electrolyte are added in sequence; The cathode is placed in an electrolytic cell to cause a selective etching reaction, and the anode powder is collected after the reaction is completed to obtain a colloidal solution of the MXene material.
6. The preparation method according to claim 4, characterized in that: A colloidal solution of the MXene material having a concentration of 2 to 5 mg / mL; The concentration of the sodium alginate solution is 3-4 mg / mL.
7. The preparation method according to claim 4, characterized in that: The conditions of the ice bath are: temperature 5-10°C, duration 7-10h; The freeze-drying conditions are: temperature -10°C to -50°C, and time 48 to 60 hours.
8. Use of the composite binder according to any one of claims 1 to 3 or the composite binder prepared by the preparation method according to any one of claims 4 to 7 in lithium ion batteries.
9. A lithium ion battery, characterized in that: The active material of the negative electrode plate is obtained by mixing silicon in a mass ratio of 6:2:2, the composite binder described in any one of claims 1 to 3 or the composite binder prepared by the preparation method described in any one of claims 4 to 7, and a conductive agent.
10. The lithium ion battery according to claim 9, characterized in that: The active material loading of the negative electrode is 0.7-1.2 mg / cm 2 .